Highly accurate Batesian mimicry of wasps dates back to the Early Oligocene and was driven by non-passerine birds - Daňková, Klára; Hadrava, Jiří; Straka, Jakub; Mikát, Michael; Exnerová, Alice; Hulva, Pavel; Nidergas, Valentin; Pecharová, Martina; Nel, André; Prokop, Jakub (Current biology, 2025)
Batesian mimicry is a widespread strategy that reduces the risk of predation of a harmless mimic by imitating a harmful model.1 Batesian mimics often vary greatly in how accurately they resemble their models.2 However, disentangling the causes of evolutionary changes in mimetic accuracy, or lack of them, is challenging. The fossil record provides a powerful tool, although it is constrained by the quality of preservation. In particular, fossil records of accurate mimics are exceptionally rare. Here, we describe the first evidence of highly accurate wasp mimicry, in a fossil belonging to diverse group of Batesian mimics: hoverflies (Diptera, Syrphidae). The hoverfly Spilomyia kvaceki sp. nov., from the Early Oligocene (33 mya) deposits in Děčín-Bechlejovice, Czech Republic, exhibits well-preserved color pattern that closely resembles extant wasp mimics. Whether modern wasp genera could have served as its model remains uncertain. However, there is an abundant fossil record of stem-group social wasps (Palaeovespa spp.)3,4,5,6,7 that we propose as suitable models. Notably, two Palaeovespa specimens were found in the same locality as S. kvaceki,8 supporting their co-occurrence. Currently, passerine birds (Passeriformes) are considered the main selecting agent of mimicry of wasps.9 However, passerines were rare in Europe during the Early Oligocene.10 Thus, the agents selecting the earliest known highly accurate mimics of wasps were most likely non-passerines of Coraciimorphae and Apodiformes clades.10,11,12,13 In conclusion, the highly accurate mimicry of wasps originated during or at least persisted through the era of non-passerine dominance in the guild of diurnal flying insectivorous predators in the Northern Hemisphere.
Keywords: color pattern; biologická evoluce; zkameněliny; Fossils; Spilomyia; perfect mimicry; Diptera; evolution; Syrphidae; zvířata; Animals; Wasps; Vespidae; sršňovití; ptáci; Europe; Birds; Biological Evolution; fossil; mimikry; mimetic accuracy; Palaeovespa; Biological Mimicry